Hotet i vägrenen: Blomsterlupinens plats i ett svenskt kulturarvslandskap - Frihammar, Mattias; Kaijser, Lars; Lagerqvist, Maja (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
Invasive species are flowers or animals that have moved from one "origin" area to a new region, often with the help of humans. This article focus on the work of reducing lupines in the county of Dalarna. The example is used as a test case to explore what a cultural analytical interpretation can provide to the discussion of invasive species: How did the lupine come to be considered a strange element in the regional and national flora? What are the social, cultural and biological contexts that makes the flower threatening? We identify the work of reducing invasive species to be part of an ecological memory complex. To this, we argue for a critical heritage perspective as a rewarding way of understanding such questions, practices and discourses.